Problems of Learning Tarakib (Phrases) Arabic for Elementary Education Students - Ziaul Khairi; Zulheddi Zulheddi; Salminawati Salminawati (Jurnal Basicedu, 2023)
Learning Tarakib (phrases) in Arabic still leaves various problems, especially for students at the elementary education level. This study aims to explain the driving and inhibiting factors for elementary school students in making Arabic tarakib sentences (phrases). This study used a qualitative approach with an analytical descriptive study method. Obtaining data through interviews, field observations, and document studies, and analyzed using data reduction techniques, data presentation, and drawing conclusions. The results showed that the students had not been able to differentiate between tarkib idhafiy and tarkib na'tiy, as was the case in isnady tarkib which included the number of ismiyyah and number of fi'liyyah, resulting in a lack of motivation, lack of enthusiasm, lack of focus in the learning process, especially learning Arabic, thus causing boredom in students in practicing Arabic both in the dormitory and in the Al-Manar Islamic boarding school complex. The implications of this study indicate that learning Arabic in the form of tarakib does not yet have the right method or strategy to be used at the basic education level. Likewise, findings about these driving and inhibiting factors can become the basis for finding models, methods or strategies for Tarakib learning for the basic education level.